AUDIT OF PROFESSIONAL MILITARY EDUCATION AS A MECHANISM FOR IMPLEMENTING NATO EDUCATION AND TRAINING STANDARDS IN UKRAINE - Kravets, Valentyna (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . The search for allies for security assurance is the key to Ukraine's existence as an independent state. Creating basis for Ukraine integration into the Euro-Atlantic security environment through the implementation of NATO education and training quality standards is one of the urgent tasks for our military education system. The purpose of this study is to substantiate the audit of professional military education as a mechanism for the implementation of NATO quality standards in Ukraine.M e t h o d s . Analysis and generalization of scholarly publications on regarding issues, alongside normative and legal documents of Ukraine and NATO, are conducted. Empirical data on the outcomes of implementing NATO's educational quality standards within educational and training facilities have been obtained from both the Education and Training Opportunities Catalogue (ETOC) and the official websites of these institutions. To scrutinize the data, descriptive statistical methods have been applied. Proposals for regulating the procedure of professional military education audit in Ukraine in alignment with NATO's quality standards have been formulated utilizing the dialectical, formal-logical and systemic-structural methods.R e s u l t s . It has established that the real prerequisites for the implementation of NATO education and training quality standards in Ukraine were created in 2022 by allocating professional military education as a part of military education system. The procedure for NATO courses certification and the structure of ETOC data on NATO-accredited educational institutions have been disclosed, thanks to which an acceptable model of the internal quality assurance system for military higher educational institutions in Ukraine has been determined, which has two components: the quality of academic education that complies with national legislation based on ESG; the quality of professional military education that meets NATO quality standards. It is proposed to conduct retraining and advanced training of military specialists in Ukraine in the form of professional military education courses Recommendations have been developed to regulate the procedure for conducting audit of professional military education in Ukraine on the basis of NATO quality standards.C o n c l u s i o n s . The purpose of implementing quality assurance standards for education and training in NATO is to ensure the compatibility of various educational institutions affiliated with Alliance. Conducting an audit of professional military education in Ukraine on the basis of NATO quality standards will contribute to the introduction of NATO-certified courses by Ukrainian military educational institutions and the development of NATO-compatible professional military education in Ukraine.
Keywords: professional military education; quality assurance, NATO institutional accreditation, NATO courses certification, audit of professional military education in Ukraine; achieving compatibility